Pausas e constituintes prosódicos na interpretação de atores - Fraga, Milena [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Introduction: In speech therapy literature the work with actors, mainly treats of organic issues involved in vocal process as misuse or vocal abuse. To a lesser extent, it is possible to find works from this same literature that address issues about acting and expressive resources, besides a few of them highlighting the importance of linguistic resources in acting. Concerning the Linguistics literature, pause is dealed from the concepts of phonetics and phonology on several language levels. In this study, we propose to observe how a linguistic resource – the pause – works in theatrical acting. Bounded by the Speech Therapy field, we seek to theoretical facts from the field of Linguistics, but essentially from Prosodic Phonology. Particularly, we point out prosodic constituents: intonational phrase (I) and phonological utterance (U). Purpose: 1) Detection of the points of pause occurred in performing the same text by ten actors. 2) Data collection of the physics characteristics of pauses length. 3) Verification on how pauses length relates with where it has occurred itself, considering prosodic boundaries of intonational phrase (I) and phonological utterance (U). Methods: We have recorded a voice narration of ten different actors, which individually, performed the same single piece of text. After record transcription, a group of ten judges individually identified the points they considered to occur pauses. Only positions holding at least 70% of the votes were acceptable for use in this research. For measures of length, in seconds, it’s been defined those VVs units occurring pauses. To analyze the statistics, it’s been calculated VV’s units measures of central tendency and dispersion, in Is and Us limitations. Significance level adopted: 0,05. Results: Mean duration for I limitations was 0,77 and 1,04 for U limitations. Standard deviation for I limitations was 0,27 and 0,30...

Introdução: na literatura fonoaudiológica, o trabalho com atores volta-se, fundamentalmente, para questões orgânicas envolvidas no processo vocal, como “mau uso” ou “abuso vocal”. Em menor grau, verificam-se, nessa mesma literatura, trabalhos que destacam questões sobre interpretação e recursos expressivos, além de poucos que destacam a importância dos recursos linguísticos na interpretação. Já no que diz respeito à literatura linguística, a pausa é abordada sob perspectivas fonética e fonológica, relacionada a vários planos da linguagem. No presente estudo, propomos observar o funcionamento de um recurso linguístico – a pausa – na interpretação teatral. Vinculados ao campo da Fonoaudiologia, buscamos subsídios teóricos no campo da Linguística, sobretudo da Fonologia Prosódica. Mais especificamente, destacamos os constituintes prosódicos frase entonacional (I) e enunciado fonológico (U). Objetivos: (1) detectar o local de ocorrência de pausas na interpretação que dez atores fazem de um mesmo texto; (2) levantar as características físicas de duração dessas pausas; (3) verificar em que medida a duração da pausa se relaciona com seu ponto de ocorrência, no que diz respeito a limites prosódicos de frases entonacionais (I) e de enunciados fonológicos (U). Metodologia: utilizamos registros em áudio de dez atores, que interpretaram, individualmente, um mesmo fragmento de um texto teatral. Após tais gravações serem transcritas, um grupo de dez juízes identificou, sem que um conhecesse o julgamento do outro, os pontos onde julgaram haver ocorrência de pausas. Foram considerados, para análise, os pontos detectados por, no mínimo, 70% dos juízes. Quanto às medidas de duração, em segundos, foi realizada a delimitação de unidades VVs em que havia ocorrência de pausas. Para análise estatística, foram calculadas medidas de tendência central e de dispersão da duração das unidades...
Keywords: Voz; Comunicação oral; Representação teatral; Fonoaudiologia; Versificação